Inactivation of CES1 Blocks Prostaglandin D(2) Glyceryl Ester Catabolism in Monocytes/Macrophages and Enhances Its Anti-inflammatory Effects, Whereas the Pro-inflammatory Effects of Prostaglandin E(2) Glyceryl Ester Are Attenuated - Scheaffer, Hannah L. (ACS Omega, 2020)
[Image: see text] Human monocytic cells in blood have important roles in host defense and express the enzyme carboxylesterase 1 (CES1). This metabolic serine hydrolase plays a critical role in the metabolism of many molecules, including lipid mediators called prostaglandin glyceryl esters (PG-Gs), which are formed during cyclooxygenase-mediated oxygenation of the endocannabinoid 2-arachidonoylglycerol. Some PG-Gs have been shown to exhibit anti-inflammatory effects; however, they are unstable compounds, and their hydrolytic breakdown generates pro-inflammatory prostaglandins. We hypothesized that by blocking the ability of CES1 to hydrolyze PG-Gs in monocytes/macrophages, the beneficial effects of anti-inflammatory prostaglandin D(2)-glyceryl ester (PGD(2)-G) could be augmented. The goals of this study were to determine whether PGD(2)-G is catabolized by CES1, evaluate the degree to which this metabolism is blocked by small-molecule inhibitors, and assess the immunomodulatory effects of PGD(2)-G in macrophages. A human monocytic cell line (THP-1 cells) was pretreated with increasing concentrations of known small-molecule inhibitors that block CES1 activity [chlorpyrifos oxon (CPO), WWL229, or WWL113], followed by incubation with PGD(2)-G (10 μM). Organic solvent extracts of the treated cells were analyzed by liquid chromatography with tandem mass spectrometry to assess levels of the hydrolysis product PGD(2). Further, THP-1 monocytes with normal CES1 expression (control cells) and “knocked-down” CES1 expression (CES1KD cells) were employed to confirm CES1’s role in PGD(2)-G catabolism. We found that CES1 has a prominent role in PGD(2)-G hydrolysis in this cell line, accounting for about 50% of its hydrolytic metabolism, and that PGD(2)-G could be stabilized by the inclusion of CES1 inhibitors. The inhibitor potency followed the rank order: CPO > WWL113 > WWL229. THP-1 macrophages co-treated with WWL113 and PGD(2)-G prior to stimulation with lipopolysaccharide exhibited a more pronounced attenuation of pro-inflammatory cytokine levels (interleukin-6 and TNFα) than by PGD(2)-G treatment alone. In contrast, prostaglandin E(2)-glyceryl ester (PGE(2)-G) had opposite effects compared to those of PGD(2)-G, which appeared to be dependent on the hydrolysis of PGE(2)-G to PGE(2). These results suggest that the anti-inflammatory effects induced by PGD(2)-G can be further augmented by inactivating CES1 activity with specific small-molecule inhibitors, while pro-inflammatory effects of PGE(2)-G are attenuated. Furthermore, PGD(2)-G (and/or its downstream metabolites) was shown to activate the lipid-sensing receptor PPARγ, resulting in altered “alternative macrophage activation” response to the Th2 cytokine interleukin-4. These findings suggest that inhibition of CES1 and other enzymes that regulate the levels of pro-resolving mediators such as PGD(2)-G in specific cellular niches might be a novel anti-inflammatory approach.